Sectoral composition, export trade partners and value added: An input-output analysis for Brazil and Mexico Patieene Alves-Passoni - United Nations Economic Commission for Latin America; the Caribbean (CEPAL Review, 2024)
This study examine the impact of changes in the sectoral composition of exports and in trade partners on the value added of Brazil and Mexico between 2000 and 2019, within the framework of Latin American structuralism. Employing quantitative input-output structural decomposition analysis, we identify shifts in value added coefficients, production techniques, domestic demand and exports (level, product mix and trade partners). The research brings out a significant correlation between changes in trade partners and the structure of the export basket. Both Brazil and Mexico display export concentration, geographically and sectorally. While alterations in the export basket and trade partners had a negative impact on Mexico’s value added growth, Brazil experienced a positive effect. This finding for Brazil is attributed in part to its specialized agricultural and mineral exports to China. Conversely, Mexico’s specialization in transport equipment exports to the United States and Canada contributed to its unfavourable outcome.